Collision probability prediction algorithm for cooperative overtaking based on TTC and conflict probability estimation method. (17th May 2019) - Chen, Junlan; Wang, Ke; Xiong, Zhoubing
This paper focuses on the feasibility and methodology of critical issues of overtaking behaviour using inter-vehicle communication technology. The main innovation of this work is the integration of a collision probability model with the overtaking procedure. In detail, the overtaking process was divided into two successive stages: the approaching stage and surpassing stage. In the approaching stage, linear assumption between collision probability and time to collision (TTC) was proposed to release the computational load. While, in the surpassing stage, conflict probability estimation method is utilised as the safety quantitative indicator to estimate the collision probability. To support the proposed method, we run many experiments on synthetic data. The result shows that our method achieves better accuracy especially in unpredictable nature of road environment, including the capability of making correct behaviour decisions and avoiding collisions with nearby vehicles, which make the proposed method sufficient for real-world implementation.